Pengaruh Implementasi Just In time, Total Quality Management dan Teknologi Informasi terhadap Kinerja Operasional pada Pabrik Gula Takalar: The Effect of Just In Time Implementation, Total Quality Management and Information Technology on Operational Performance at the Takalar Sugar Factory - Pratiwi, Andi Monika; Abdullah, Wahidah; Ahmad, S Widad (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This research aims to determine the partial and simultaneous influence of just in time implementation, total quality management and information technology on operational performance at the Takalar sugar factory. This research uses primary data and secondary data, the sampling technique used in this research is probability sampling using simple random sampling and using the Slovin formula with a sample size of 127 respondents in this research. The type of research used is quantitative research. In this research, it uses Structural Equation Modeling (SEM) using SmartPLS version 3.0 for Windows as a data analysis technique. Based on the results of the research that has been conducted, it shows that the implementation of just in time has a positive and significant effect on operational performance, the implementation of total quality management has a positive and significant effect on operational performance, the implementation of information technology has a positive and significant effect on operational performance, and the implementation of just in time, total quality Management and information technology have a simultaneous influence on operational performance at the Takalar sugar factory.